The use of vacuum degassing for heating and cooling installations and its impact on energy efficiency - Radomski, Bartosz; Mróz, Tomasz (Instal, 2024)
Degassing is a critical maintenance procedure for heating and cooling water systems. By effectively removing dissolved gases and entrapped air, degassing ensures optimum heat transfer efficiency, reduces corrosion and noise, prevents airlocks and cavitation, and extends the life of system components. The use of methods such as manual venting, automatic venting, vacuum venting, thermal venting, and centrifugal separators can significantly improve the efficiency and reliability of heating systems. The use of a vacuum venting system and a dirt separator increases energy efficiency which implicates reduced energy consumption. The vacuum venting system alone can increase the energy efficiency of heating systems, up to 4.7% for radiator systems, up to 5.1% for underfloor heating systems, and up to 4.2% for refrigeration systems. The vacuum venting system together with a vacuum dirt separator can increase the energy efficiency of heating systems, up to 6.5% for radiator systems, up to 10.6% for underfloor heating systems, and up to 10.3% for refrigeration systems. The use of vacuum degassing contributes to the achievement of sustainable development goals, reduces energy consumption and thus reduces CO2 emissions into the environment, and also allows for a significant reduction in operating costs with low investment costs and ease of application of the solution.
Keywords: vacuum degassing; energy analysis; energetic efficiency